Advances in computers., volume 65 - Zelkowitz, Marvin V., 1945- ([S.l.] : Academic Press, 2005)
This present volume describes some of the latest advances in the computer science field today. This current volume emphasizes information processing with chapters on artificial intelligence, data bases and software engineering. In particular it looks at the interfaces between AI and software development with chapters on how AI affects the development of correct programs, and conversely, how software engineering can affect the development of correct AI programs. Key Features: * In-depth surveys and tutorials on new computer technology. * Well-known authors and researchers in the field. * Extensive bibliographies with most chapters. * Impact of AI on software development and impact of software development on correct AI programs. * What is the educational role of mathematics in the development of the next generation of computer professional? * In-depth surveys and tutorials on new computer technology. * Well-known authors and researchers in the field. * Extensive bibliographies with most chapters. * Impact of AI on software development and impact of software development on correct AI programs. * What is the educational role of mathematics in the development of the next generation of computer professional?
Preface. -- Contributors. -- Chapter 1. The state of artificial intelligence by Adrian A. Hopgood -- Chapter 2. Software model checking with SPIN by Gerard J. Holzmann -- Chapter 3. Early Cognitive Computer Vision by Jan-Mark Geusebroek -- Chapter 4. Verification and Validation and Artificial Intelligence by Tim Menzies and Charles Pecheur -- Chapter 5. Indexing, Learning and Content-based Retrieval for Special Purpose Image Databases by Mark J. Huiskes and Eric J. Pauwels -- Chapter 6. Defect Analysis: Basic Techniques for Management and Learning by David N. Card -- Chapter 7. Function Points by Christopher J. Lokan -- Chapter 8. The Role of Mathematics in Computer Science and Software Engineering Education by Peter B. Henderson.
Keywords: Electronic data processing; Computers; Electronic books